Effects of Dietary Flaxseed Oil and Ascorbic Acid on the Reproductive Performance of South African Indigenous Sheep - Jabulani Nkululeko Ngcobo; Tshimangadzo Lucky Nedambale; Khathutshelo Agree Nephawe; Tlou Caswell Chokoe; Fhulufhelo Vincent Ramukhithi (Ruminants, 2023)
The current study aimed to evaluate the effects of the dietary inclusion of flaxseed oil and ascorbic acid on the reproductive performance of South African indigenous sheep (Ovis aries). Twenty-two matured South African indigenous rams (eight BaPedi, nine Zulu, and five Namaqua Afrikaner; age of 6 years and body weight of 64.4 ± 1.6 kg) were randomly assigned into five treatment groups (NC (standard diet), PC (basal diet), FO (5% flaxseed oil), AA (4% ascorbic acid), and FO + AA (5% flaxseed oil + 4% ascorbic acid)). Semen samples were collected during the natural breeding season using an artificial vagina. Semen samples were evaluated for macroscopic (semen volume, pH, and sperm concentration) and microscopic (morphology, malondialdehyde, membrane permeability, and sperm cell motility parameters) characteristics. Eighty-one South African indigenous ewes were synchronized using controlled intravaginal drug devices impregnated with 0.3 g progesterone for 10 days and then injected with 300 IU of Pregnant Mare Serum Gonadotropin. These ewes were then hand-mated. The data were subjected to the General Linear Model (GLM) in Minitub® 2017. A cross-tabulated Chi-Squared (χ2) test was used to track the frequencies of the conception rate. Treatment means were separated using Student’s Least Significant Difference (LSD) and considered significantly different when the p-value was less than 0.05. No considerable breed effect was observed for semen volume, semen pH, sperm concentration, intact membrane, and non-intact membrane. FO + AA led to higher semen volume (1.05 ± 0.06 mL), intact sperm membranes (88.83 ± 1.27%), and low malondialdehyde levels (0.37 ± 0.04 nmol/mL) in comparison to other treatment groups. Total sperm motility was higher in FO + AA (95.81 ± 0.80%) compared to FO, AA, PC, and NC. The conception rate was higher in FO (94%), AA (94%), and FO + AA (100%) when compared to NC (71%) and PC (79%). The testosterone concentration did not differ among PC, FO, AA, and FO + AA. It was concluded that the inclusion of 5% flaxseed oil (FO and FO + AA) improves both the semen quality and the conception rate of South African indigenous sheep.